An electrical microenvironment constructed based on electromagnetic induction stimulates neural differentiation. (13th March 2023) - Qi, Fangwei; Liao, Ruobing; Wu, Ping; Li, Huixing; Zan, Jun; Peng, Shuping; Shuai, Cijun
Abstract : A NH2 -MXene/PLLA nerve conduit with a conductive network structure is constructed by laser additive manufacturing, which can generate electrical signals driven by electromagnetic induction, and the generated electrical signals can promote the differentiation of nerve cells. Abstract : Electrical stimulation is considered an effective way to accelerate peripheral nerve cell growth. However, reliance on external wires and a power supply restricts its further applications. In this work, a wireless magnet-powered electrical stimulation system was constructed based on the electromagnetic induction effect. Specifically, amino-functionalized conductive MXene nanosheets were first wrapped on the PLLA particles' surface by electrostatic assembly. Then the conductive NH2 -MXene/PLLA conduit was fabricated by laser additive manufacturing. Triggered by a rotating magnetic field, the conduit could act as a coil to cut magnetic induction lines, converting magnetic energy into electrical energy and thereby achieving wireless electrical stimulation. The results indicate that the conduit presented an excellent conductivity of 8.44 S m −1, benefiting from its formed conductive network structure. Under excitation of the rotating magnetic field, the conduit generated an electric current of 10 μA, which is in the appropriate range for nerve cell growth. An in vitro cell test confirmed that the generated current effectively enhanced the PC12 cell proliferation, neurite growth and differentiation-related mRNA (Nestin, MAP2 and Tuj1) expression. Moreover, it also promoted PC12 cells to differentiate into mature neurons, evidenced by calcium sparks produced in PC12-derived neurons. Collectively, this wireless electrical stimulation system offers a new perspective on peripheral nerve repair.